Limiting Behavior of the Partial Sum for Negatively Superadditive Dependent Random Vectors in Hilbert Space - Mi-Hwa Ko (Journal of Mathematics)
In this paper, We study the complete convergence and Lp- convergence for the maximum of the partial sum of negatively superadditive dependent random vectors in Hilbert space. The results extend the corresponding ones of Ko (Ko, 2020) to H-valued negatively superadditive dependent random vectors.